Regional changes in brain apparent diffusion coefficient in fetuses with complex congenital heart disease and normal pregnancy assessed using diffusion-weighted imaging - Song, Jia-Guang; Sun, Cong; Zhu, Mei; Zhu, Jin-Xia; Zhang, Nan; Wang, Guang-Bin; Zhao, Bin (Frontiers in Neurology, 2023)
Objectives: To explore changes in brain apparent diffusion coefficient (ADC) in normal fetuses and fetuses with complex congenital heart disease (CHD) during the second and early third trimesters. Methods: This single-center prospective study was conducted from May 2019 through October 2021. We measured and compared the mean ADC values between 23 fetuses with CHD and 27 gestational age (GA)-matched controls using covariance analyses. ADC density plots and histograms were used to compare brain characteristics. False-discovery rates (FDR, α = 0.05) correction was used for multiple testing. Results: The mean ADC in the frontal white matter, temporal white matter, parietal white matter, occipital white matter, cerebellar hemisphere, central area of the centrum semiovale, basal ganglia region, thalamus, and pons were not significantly different (all P > 0.05). Based on histogram analysis, there were no significant differences between the controls and fetuses with CHD after FDR correction. However, the ADC density plots showed significant heterogeneity between the controls and fetuses with CHD. Conclusions: The mean ADC values and ADC histogram analysis did not differ between the CHD and normal groups. The ADC density plots may provide supplementary information and improve the sensitivity for detecting early brain changes in fetuses with CHD.